Transformational Leadership and Work Discipline as Drivers of Employee Performance - Eka Kusuma Mustikoaji Sinaga; Editya Nurdiana (Siber International Journal of Digital Business (SIJDB), 2026)
This study examines how leadership and behavioral discipline contribute to employee performance in the logistics industry. The research object is employees of PT Triglobal Mandiri Indonesia, a national logistics and distribution company operating in a time‑sensitive and coordination‑intensive environment. The objective of this study is to analyze the direct effects of transformational leadership and work discipline on employee performance, to examine their influence on the quality of leader–employee relationships, and to test the mediating role of leader–member exchange. This study employed a quantitative associative research design using a structured questionnaire distributed to 100 employees, with data analyzed through Partial Least Squares–Structural Equation Modeling. The results show that transformational leadership and work discipline have a positive and significant direct effect on employee performance. Transformational leadership also significantly influences leader–member exchange, while work discipline does not. Leader–member exchange has a positive effect on performance; however, it does not mediate the relationship between transformational leadership and performance nor between work discipline and performance. The study concludes that employee performance in logistics companies is driven primarily by direct leadership practices and disciplined work behavior, while relationship quality plays a supportive but non‑mediating role.